The Impact of Compulsory Schooling on Earnings. Evidence from the 1999 Education Reform in Poland - Jacek Liwiński (Global Labor Organization (GLO), 2018)
In 1999, a reform of education was implemented in Poland, which added one year to the shortest available educational path, leading to the acquisition of basic vocational education. In the new system, students choosing this path acquire one more year of general education, which, according to the authors of the reform, should improve the student's position in the labor market, as the inadequate general skills were identified as the main deficit of basic vocational education prior to the reform. Using the regression discontinuity design and data from the Polish LFS, we find that an additional year of general education has led to an increase in hourly wages of men, but not of women, who completed basic vocational schools.
Keywords: I21; I26; J24; 330; education; schooling; earnings; regression discontinuity design